DJI Company / Muhammad Mustaqeem Mashasan - Mashasan, Muhammad Mustaqeem (2022)
Technological development can be defined as the application of information intended to design and use the goods and services. The study of technology entrepreneurship serves an important function beyond satisfying intellectual curiosity. This case study reports the findings of a thorough study of a company use technology in the business. This case study reports that the results of a comprehensive study of companies using technology in business are very high. Furthermore, this case study purposely to find the innovation of technology used in entrepreneurship which can be developed in business whether it is a global or small business. Besides, this study intends to innovate the use of technology in business to become effective and interesting. Therefore, this study case intends to make improvement of existing drone by implementing technological solution. In this case study, the idea is to improve the existing spy drone is developing an autopilot spy drone integrated with artificial intelligence. This case study targeted DJI company for company analysis which require to analyse their company background, their products which is a drone and how their business, marketing and operational are done. This case study also had analysed company by using SWOT analysis to define their strengths, weakness, opportunities, and threats.